2007
DOI: 10.1001/archsurg.142.12.1202
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Enucleation of Insulinomas

Abstract: Laparoscopic enucleation of insulinomas is safe and effective and is associated with a short hospital stay.Design: Case series identified through retrospective review of medical records.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 8 publications
0
41
1
4
Order By: Relevance
“…However, many high-degree malignant cases, such as pancreatic ductal adenocarcinoma, were also reported in Lap PD. Lap EN is mostly applied to insulinoma and some rare cases, such as nonfunctioning neuroendocrine tumors [16][17][18]. Mabrut [19] reviewed 127 laparoscopic pancreatic operations in 25 European medical centers and found that 87% of the cases were benign tumors.…”
Section: Indicationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many high-degree malignant cases, such as pancreatic ductal adenocarcinoma, were also reported in Lap PD. Lap EN is mostly applied to insulinoma and some rare cases, such as nonfunctioning neuroendocrine tumors [16][17][18]. Mabrut [19] reviewed 127 laparoscopic pancreatic operations in 25 European medical centers and found that 87% of the cases were benign tumors.…”
Section: Indicationmentioning
confidence: 99%
“…The average hospital stay was 18 days (range: 7-39 days), and the average conversion rate was 46% (range: 12%-100%). The mean number of lymph nodes in the pathology was 19 (range: [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The complication rates were 16% and mortality was recorded in only 2 (1.3%) patients during the perioperative period.…”
Section: Lap Pdmentioning
confidence: 99%
“…Furthermore, reports show intraoperative ultrasound (IOUS) to be useful for detecting and localizing insulinomas, with an accuracy of 83-100% (Level II-III) [20][21][22][23][24][25] Sensitivity has been reported to be better than that of preoperative angiography. Recent publications also confirm the ability of LUS to detect neuroendocrine tumors of the pancreas as small as 3-5 mm in diameter [23,26,27]. The ability of intraoperative ultrasound to detect extrahepatic gastrinoma is lower (about 58%) (Level III) [28,29].…”
Section: Risks and Benefitsmentioning
confidence: 86%
“…Pancreatic resection using the laparoscopic approach has been reported recently [17,18,19,20]. A patient with solid and cyst-papillary neoplasm who underwent laparoscopic partial resection was experienced in our institute.…”
Section: Discussionmentioning
confidence: 99%